Tomographic Analysis and Modeling of Polymer Electrolyte Fuel Cell Unsupported Catalyst Layers. Issue 2 (1st January 2018) - Ishikawa, Hiroshi; Henning, Sebastian; Herranz, Juan; Eychmüller, Alexander; Uchida, Makoto; Schmidt, Thomas J.
Abstract : Polymer electrolyte fuel cells' (PEFCs) widespread commercialization is hindered by the devices' limited durability, in terms caused by the corrosion of the carbon support used in the Pt-based PEFC catalysts. Using unsupported electrocatalysts could mitigate such durability issues, but little is known regarding the manner in which their processing into catalyst layers (CLs) affects pore size distribution (PSD) and PEFC performance. Thus, we have used a computational model to investigate the modes of agglomerate packing in CLs made from unsupported Pt3 Ni nanochain ensembles (aerogels) or Pt black, and complemented this analysis with focused ion beam scanning electron microscopy tomography of corresponding real CLs. 3D structures, PSDs and tortuosities were obtained for real and computed CLs and were found to be in good agreement. The Pt black CL mainly exhibits large and straight pores (>100 nm wide), while the Pt3 Ni aerogel CL mostly features small and twisted pores (< 100 nm wide) that cause the significantly poorer O2 mass transport (vs. Pt black) observed in PEFC experiments. Moreover, this modeling approach leads to key insights on the working principle of a filler material used for positively shifting the average PSD and improving the PEFC performance of the Pt3 Ni CL.